2012
DOI: 10.4103/0970-0358.96602
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and demographic profile of the cleft lip and palate in Sub-Himalayan India: A hospital-based study

Abstract: Objectives:To study the cleft lip and cleft palate in the poverty stricken Sub-Himalayan Garhwal region of India, being a commonly seen congenital abnormality and scarcity of studies about the demography of cleft in this region.Design:A prospective cohort observational case series was performed on 4657 cleft patients at a Tertiary care Hospital in Dehradun, India, over a period of 5 years.Outcome measures:The authors investigated the differences between age and sex with cleft status and family history of cleft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 15 publications
6
32
0
1
Order By: Relevance
“…Studies have reported that consanguinity is commonly practiced by people who are illiterate and from low socioeconomic status and other related factors. [5,10,24] Rural areas show higher rates of illiteracy and low socioeconomic status in India. [25] Despite the several negative consequences of the practice ranging from neonatal mortality to congenital anomalies with genetic mutations, consanguinity also offers certain social advantages seen in rural areas such as ease of enhanced female autonomy, marriage arrangements, more stable marital relationships, lower domestic violence, greater compatibility with in-laws, economic benefits of reduced dowry, lower divorce rates and maintenance of any landholding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that consanguinity is commonly practiced by people who are illiterate and from low socioeconomic status and other related factors. [5,10,24] Rural areas show higher rates of illiteracy and low socioeconomic status in India. [25] Despite the several negative consequences of the practice ranging from neonatal mortality to congenital anomalies with genetic mutations, consanguinity also offers certain social advantages seen in rural areas such as ease of enhanced female autonomy, marriage arrangements, more stable marital relationships, lower domestic violence, greater compatibility with in-laws, economic benefits of reduced dowry, lower divorce rates and maintenance of any landholding.…”
Section: Discussionmentioning
confidence: 99%
“…[10,22,26] The OFC common in Hindus was again in harmony with results reported by Dvivedi and Dvivedi. [24] The Hindu Code Bill of 1984 and the Hindu Marriage Act of 1955 support the legality of consanguineous marriages in India. [7] The high prevalence rate in the Hindu religion is in proportion to the national population, which is about 80.5% according to 2011 census.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and prevalence of CL±P are 1 in 600 (1:600) and 9.92 per 10,000 worldwide respectively. The CL and CLP prevalence are 3.28 per 10,000 & 6.64 per 10,000 [3]. In India, the number of infants born with CL±P is 28,600 per year (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A family history of the CLP has increased risk for development of CLP; while in CP, the risk is the same as a general population [5] Organizations like the Smile Train is working for the welfare of the CL±P patients worldwide [6]. The problem that CL±P deformity poses in India is different from the developed countries because of poverty and illiteracy [3]. Understanding variation of prevalence, region, nutrition, socioeconomic strata and ethnicity wise distribution will help to plan future course of action to improve cleft care.…”
Section: Introductionmentioning
confidence: 99%
“…For all such children, the problem goes beyond the obvious disfigurement of the face to repeated infections, social stigma, problems with speech, hearing, and teeth formation. (3) These children are often teased by their friends and they lose self-confidence. They suffer with emotional "burn out" in adolescence.…”
Section: Introductionmentioning
confidence: 99%